2017
DOI: 10.1007/s12110-017-9297-8
|View full text |Cite
|
Sign up to set email alerts
|

Interethnic Interaction, Strategic Bargaining Power, and the Dynamics of Cultural Norms

Abstract: Ethnic groups are universal and unique to human societies. Such groups sometimes have norms of behavior that are adaptively linked to their social and ecological circumstances, and ethnic boundaries may function to protect that variation from erosion by interethnic interaction. However, such interaction is often frequent and voluntary, suggesting that individuals may be able to strategically reduce its costs, allowing adaptive cultural variation to persist in spite of interaction with out-groups with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 46 publications
(49 reference statements)
0
59
0
1
Order By: Relevance
“…The interaction effect had a mean large effect size ranging from a small effect to a very large effect (g*=2.549 [0.211, 5.066]; Figure 3C and 3D). The 95% HPD of the interaction effect excluded 0, indicating that this was a robust effect (Bunce and McElreath, 2017;McElreath, 2018). Simple main effect analyses showed that the direction of the interaction was as expected.…”
Section: The Task-dependent Modulation Of Left Vmgb Increased For Recmentioning
confidence: 61%
See 2 more Smart Citations
“…The interaction effect had a mean large effect size ranging from a small effect to a very large effect (g*=2.549 [0.211, 5.066]; Figure 3C and 3D). The 95% HPD of the interaction effect excluded 0, indicating that this was a robust effect (Bunce and McElreath, 2017;McElreath, 2018). Simple main effect analyses showed that the direction of the interaction was as expected.…”
Section: The Task-dependent Modulation Of Left Vmgb Increased For Recmentioning
confidence: 61%
“…The HPD is the probability that the mean lies within the interval (Gelman et al, 2013;McElreath, 2018), this means that we are 95% sure the mean lies within the specified interval bounds. If the posterior probability distribution of odds ratios does not strongly overlap one (i.e., the HPD excludes one), then it is assumed that there is a detectable difference between conditions (Bunce and McElreath, 2017;McElreath, 2018).…”
Section: Behavioural Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The lower row contains analogous sample sizes for Mestizos. Further explanation, ethnographic validation, and translations of these questions are provided in Supplementary descriptions of these communities can be found in Bunce and McElreath (2017), Shepard et. al 2010, and Llosa Isenrich and Nieto Degregori (2003).…”
Section: Study Populationmentioning
confidence: 99%
“…De esa manera, como señala Stavenhagen (1968), en el "sistema de relaciones interétnicas" pueden instarse reconfiguraciones en las relaciones comerciales, en los modos de estratificación social y en los mecanismos de movilidad social. En este sentido, Bunce y McElreath (2017) hacen hincapié en los métodos y contenidos educativos; Villar, Jiménez y Alioto (2015) en el manejo y enseñanza de la lengua local, y Rodríguez (2002) y Oehmichen (2005) en la formación familiar y la identidad y género, respectivamente.…”
unclassified